Expression of suppressor of cytokine signaling 1 and 3 in ligature-induced periodontitis in rats - Chaves de Souza, Joao Antonio [UNESP]; Boas Nogueira, Andressa Vilas [UNESP]; Chaves de Souza, Pedro Paulo [UNESP]; Cirelli, Joni Augusto [UNESP]; Garlet, Gustavo Pompermaier; Rossa, Carlos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Objective: : Evaluate expression of inducible negative regulators of JAK/STAT pathway and their target proteins during the course of ligature-induced experimental periodontal disease in rats.Design: : Rats were sacrificed 07, 15 and 30 days after disease induction for histological evaluation of periodontal inflammation and macroscopic analysis of alveolar bone loss. SOCS expression and the activation status of STAT1 and STAT3 were evaluated in gingival biopsies by real time PCR and Western blot.Results: : Ligature-induced model presented significant progressive bone loss from 7 to 30 days. Inflammation was evident and similar for 07 and 15 days; however, a decrease on severity at the end of the experimental period was observed. There was a significant (p < 0.05) increase on SOCS1 and SOCS3 gene expression in PD compared to control group at 15 and 30 days. The SOCS1 and SOCS3 protein expression and activation of STAT1 and STAT3 were increased in earlier periods in the ligature model.Conclusion: : This study suggests that SOCS1 and SOCS3 were directly correlated with regulatory mechanism of the inflammatory process responsible for the periodontal disease destruction. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Signal transduction; STAT transcription factors; Janus kinases; Suppressor of cytokine signaling proteins; Periodontal disease